Unlearning To Teach Mathematics. Issue Paper 88-1 - Ball, Deborah Loewenberg, 1954-; National Center for Research on Teacher Education, East Lansing, MI. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
In spite of courses and workshops, beginning teachers are most likely to teach mathematics just as they were taught. Changes in certification requirements, such as expecting teachers to complete more coursework, or improvements in curriculum materials, such as programs that emphasize problem solving, have also been insufficient to alter the prevailing patterns of math teaching and learning in schools. Teacher preparation can be a more effective intervention if it is based on a conception of the teacher as learner, taking into account what teacher candidates bring with them related to mathematics and the teaching and learning of math. To do that, we need to know more about these learners and to develop effective strategies for working with them. This paper describes a project implemented in an introductory teacher education course, a project designed to bring to the surface and challenge what entering teacher candidates know about mathematics and how it is taught and learned. With illustrations from the responses of participating teacher education students, the author outlines a conceptual framework for the question, "What do prospective teachers bring with them to their professional education that is likely to affect their learning to teach mathematics?" The paper concludes with a discussion of the implications of this perspective for research and practice in teacher education. (Author)
Availability: National Center for Research on Teacher Education, 116 Erickson Hall, College of Education, Michigan State University, East Lansing, MI 48824-1034 ($3.00).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Teachers.
Researchers.
Administrators.
Practitioners.
Keywords: Course Content; Educational Improvement; Elementary School Mathematics; Elementary Secondary Education; Mathematics Instruction; Preservice Teacher Education; Program Descriptions; Secondary School Mathematics; Teacher Education Curriculum; Teaching Methods; Reports, Descriptive